Design and analysis of high-speed coreless axial flux permanent magnet generator with circular magnets and coils - Fei, Wei-Zhong; Luk, Patrick Chi-Kwong; Jinupun, Ken (Cranfield University, 2010)
A high-speed coreless surface mounted axial flux permanent magnet generator with circular magnets and coils is proposed and studied. The performances of the machine are estimated and optimised by approximate theoretical analysis and comprehensive three-dimensional (3D) electromagnetic finite element analysis (FEA). Mechanical stresses in the rotor disc developed at high rotational speed are analysed and evaluated by 3D mechanical FEA to ensure the rotor's integrity. Finally, a prototype machine is constructed and tested. Both the experimental and predicted results have shown that the proposed generator possesses distinct advantages such as simple structure and high efficiency. The prototype also demonstrates its utility as a very low-cost generator.